Beginning BlackBerry development - Rizk, Anthony (Berkeley, Calif. Apress New York Distributed to the book trade by Springer-Verlag, 2009)
"This book will teach you how to build Java-based BlackBerry applications, starting from the very basics all the way through packaging and distributing, giving you enough knowledge to produce useful, real-world applications." --Publisher's description.
Setting the stage -- Hello world -- What makes a BlackBerry application? -- User interface basics -- Beyond the basics of user interfaces -- Storing data -- Hello out there! Making a network-enabled application -- Where am I? Using location-based services -- Getting your app out there: packaging and publishing -- Next steps.
Includes index.
"Learn how to build Java-based BlackBerry applications from scratch"--Cover
"Books for professionals by professionals"--Back Cover.
"Companion eBook available"--Spine.
Includes index.
Keywords: BlackBerry (Smartphone) -- Programming; Computer software -- Development; Mobile computing; Cell phones; Pocket computers; BlackBerry (Smartphone) -- Computer software; Smartphones -- Computer software; Application software -- Design